2012
DOI: 10.1177/019874291203700306
|View full text |Cite
|
Sign up to set email alerts
|

Coping Power Dissemination Study: Intervention and Special Education Effects on Academic Outcomes

Abstract: This study examines whether a school-based preventive intervention for children with aggressive behavior affects children's academic outcomes when it is implemented by school counselors in a dissemination field trial. The Coping Power program targets empirical risk factors for aggressive behavior and focuses primarily on teaching social and emotional skills rather than directly intervening around academic performance. This study examined the long-term effects (2 years postintervention) of Coping Power on langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Lochman (1992) found that aggressive boys had lower rates of self-reported substance use three years after involvement in the Anger Coping program. Although these latter findings from controlled trials are encouraging, the only long-term follow-up study of focused targeted prevention programs with an “unbiased” measure such as school records and blinded teacher ratings found that Coping Power children had lower teacher-rated aggression and academic problems (Lochman, Wells, Qu & Chen, in press), and less deterioration in language arts grades (Lochman, Boxmeyer, Powell, Qu, Wells & Windle, 2012) across time in comparison to a control condition in a three-year follow-up.…”
Section: Longer-term Follow-up Effects Of Targeted Prevention Programsmentioning
confidence: 99%
“…Lochman (1992) found that aggressive boys had lower rates of self-reported substance use three years after involvement in the Anger Coping program. Although these latter findings from controlled trials are encouraging, the only long-term follow-up study of focused targeted prevention programs with an “unbiased” measure such as school records and blinded teacher ratings found that Coping Power children had lower teacher-rated aggression and academic problems (Lochman, Wells, Qu & Chen, in press), and less deterioration in language arts grades (Lochman, Boxmeyer, Powell, Qu, Wells & Windle, 2012) across time in comparison to a control condition in a three-year follow-up.…”
Section: Longer-term Follow-up Effects Of Targeted Prevention Programsmentioning
confidence: 99%
“…Coping Power is typically delivered in small groups, but individual delivery can produce stronger effects in the school setting for some children (Lochman et al, 2015). The intervention has helped to prevent the declines seen in control children in language arts grades in the two years following intervention (Lochman et al, 2012). Long-term follow-up effects, three to four years after the intervention, have been found on youths’ externalizing behavior in school settings in two separate studies (Lochman et al, 2013, 2014) and on substance use in a clinic setting (Zonnevylle-Bender et al, 2007).…”
Section: Coping Power Programmentioning
confidence: 99%
“…16 Furthermore, CP has been developed for use at different levels of intervention: targeted prevention, universal prevention and clinical intervention levels. [17][18][19][20] The purpose of the present study was to evaluate the efficacy of a preschool version of the CP universal curriculum utilizing a randomized clinical trial. The CP conceptual model, principles and practices were preserved, but the curriculum components were modified to be developmentally appropriate for preschool children.…”
Section: Intervention Programmes For Preschoolersmentioning
confidence: 99%
“…Several studies documented CP effectiveness in reducing children's behavioural difficulties at school, as well as in reducing students' risk for later delinquency and substance use . Furthermore, CP has been developed for use at different levels of intervention: targeted prevention, universal prevention and clinical intervention levels . The purpose of the present study was to evaluate the efficacy of a preschool version of the CP universal curriculum utilizing a randomized clinical trial.…”
Section: Introductionmentioning
confidence: 99%